Effects of melatonin on ischemia and reperfusion injury of the rat heart - Szárszoi, O; Asemu, G; Vanecek, J; Ost'ádal, B; Kolár, F (Cardiovascular drugs and therapy, 2001)
Effects of melatonin on various manifestations of ischemia/reperfusion injury of the isolated perfused rat heart were examined. Ischemia- and reperfusion-induced ventricular arrhythmias were studied under constant flow in hearts subjected to 10, 15 or 25 min of regional ischemia (induced by LAD coronary artery occlusion) and 10-min reperfusion. Melatonin was added to the perfusion medium 5 min before ischemia at concentrations of 10 micromol/l or 10 nmol/l and was present throughout the experiment. Recovery of the contractile function was evaluated under constant perfusion pressure after 20-min global ischemia followed by 40-min reperfusion. Hearts were treated with melatonin at a high concentration (10 micromol/l) either 5 min before ischemia only (M1) or 5 min before ischemia and during reperfusion (M2) or only during reperfusion (M3). At the high concentration, melatonin significantly reduced the incidence of reperfusion-induced ventricular fibrillation and decreased arrhythmia score (10% and 2.2+/-0.3, respectively) as compared with the corresponding untreated group (62% and 4.1+/-0.3, respectively); the low concentration had no effect. This substance did not affect the incidence and severity of ischemic arrhythmias. Melatonin (M2, M3) significantly improved the recovery of the contractile function as compared with the untreated group; this protection did not appear if melatonin was absent in the medium during reperfusion (Ml). Our results show that melatonin, in accordance with its potent antioxidant properties, effectively protects the rat heart against injury associated with reperfusion. It appears unlikely that melatonin is cardioprotective at physiological concentrations.
Keywords: Myocardial Reperfusion Injury; Arrhythmias, Cardiac; reperfuzní poškození myokardu; Ventricular Premature Complexes; srdeční arytmie; Male; Rats; Ventricular Fibrillation; scavengery volných radikálů; melatonin; potkani Wistar; Myocardial Ischemia; Free Radical Scavengers; Animals; komorové extrasystoly; zvířata; mužské pohlaví; fibrilace komor; ischemická choroba srdeční; krysa rodu Rattus; Rats, Wistar; Melatonin